Visual abilities distinguish level of play in rugby - Millard, L.; Shaw, B.; Breukelman, G.; Shaw, I. (Annals of Applied Sport Science, 2020)
Background. Novices in sport possesses similar visual skills to that of experts, however there may be major differences in magnitude of performance in these skills, with expert athletes only demonstrating superiority in specific vision skills and not all aspects of vision. Objectives. In this vain, the aim of this study was to discern whether Premier League rugby players has enhanced visio-spatial skills in comparison to First Division rugby players. Methods. Thus, the present study compared the performance of Premier League rugby players (n = 40) and First Division rugby players (n = 40) on six specific components of vision, namely; accommodation facility, saccadic eye movement, speed of recognition, peripheral awareness, visual memory, and hand-eye coordination. Results. Premier League rugby players performed significantly (p = 0.001) better than the First Division rugby players in five of the six tests. but were found to be similar in visual memory performance (p = 0.810). Conclusion. While this study substantiates the proposal that expert athletes, and specifically rugby players, have superior visual expertise to novice athletes, this study also found that this is not the case with all vision skills. The present study`s findings suggest that sport-specific vision testing batteries may be required to distinguish high performers from low performers in the same vein as physical tests are utilised in the selection and recruitment of athletes.